Iron Intake, Hemoglobin Level, and Red Blood Cell Indices in Adolescents with Obesity - Aviyani Aviyani; Ginna Megawati; Susi Susannah (Universitas Kristen Maranatha, 2018)
Obesity is a condition of excess and abnormal fat accumulation. Obese adolescents are atgreater risk of developing iron deficiency anemia with microcytic hypochromic red blood cells(RBC). Iron deficiency in obesity relates to low iron intake, abnormal iron absorption, andincreased iron utilization. The aim of this study was to determine iron intake, hemoglobin level,and RBC indices in faculty of medicine students with obesity. We used descriptive cross-sectional method, involving year of 2016 students in Faculty of Medicine PadjadjaranUniversity with obesity. Pregnant women and students with previous history of thallasemia oranemia were excluded. Iron intake was assessed using Food Frequency Questionnaire.Hemoglobin level and RBC indices were measured in Hasan Sadikin General Hospital. Ironintake of male subjects were adequate in 62,5% subjects and low in 37,5% subjects. Iron intakein female subjects were adequate in 20% subjects and low in 80% subjects. Male hemoglobinlevel were normal and 20% of female subjects had anemia. All male subjects were normochromnormocytic, 40% female subjects were hypochrom microcytic.Keywords: adolescents, hemoglobin level, iron intake, obesity, red blood cell indices